Case management for patients with chronic systolic heart failure in primary care: the HICMan exploratory randomised controlled trial - Peters-Klimm, Frank; Campbell, Stephen; Hermann, Katja; Kunz, Cornelia Ursula; Müller-Tasch, Thomas; Szecsenyi, Joachim (Trials, 2010)
Chronic (systolic) heart failure (CHF) represents a clinical syndrome with high individual and societal burden of disease. Multifaceted interventions like case management are seen as promising ways of improving patient outcomes, but lack a robust evidence base, especially for primary care. The aim of the study was to explore the effectiveness of a new model of CHF case management conducted by doctors' assistants (DAs, equivalent to a nursing role) and supported by general practitioners (GPs).